Demographic correlates of screen time and objectively measured sedentary time and physical activity among toddlers: a cross-sectional study - Valerie Carson; Nicholas Kuzik (BMC, 2017)
Abstract Background Determining the most important demographic correlates of sedentary behavior and physical activity will help identify the groups of children that are most in need of intervention. Little is known in regards to the demographic correlates of sedentary behavior and physical activity in toddlers (aged 12-35 months), where long-term behavioral patterns may initially be formed. Therefore, the objective of this study was to examine the associations between demographic correlates and specific types of sedentary behavior and physical activity in this age group. Methods Findings are based on 149 toddlers (19.0 ± 1.9 months) and their parents (33.7 ± 4.7 years) recruited from immunization clinics in Edmonton, Canada as part of the Parents' Role in Establishing healthy Physical activity and Sedentary behavior habits (PREPS) project. Toddlers' and parental demographic characteristics and toddlers' television viewing, video/computer games, and overall screen time were measured via the PREPS parental questionnaire. Toddlers' objectively measured sedentary time and physical activity (light, moderate to vigorous, and total) were accelerometer-derived using Actigraph wGT3X-BT monitors. Simple and multiple linear regression models were conducted to examine associations. Results In the multiple linear regression models, toddlers' age, toddlers' sex (female versus male), toddlers' race/ethnicity (other versus European-Canadian/Caucasian), and household income ($50,001 to $100,000 versus > $100,000) were significantly positively associated, and main type of child care (child care center versus parental care) was significantly negatively associated with screen time. Similar findings were observed with television viewing, except null associations were observed for toddlers' sex. Toddlers' race/ethnicity (other versus European-Canadian/Caucasian) was significantly positively associated and main type of child care (child care center, day home, other versus parental care) was significantly negatively associated with video/computer games. Toddlers' sex (female versus male) was significantly positively associated with sedentary time and significantly negatively associated with moderate- to vigorous-intensity physical activity. Conclusions Female toddlers, toddlers from ethnic minority groups, toddlers from families of lower income, and toddlers whose main type of child care is not center-based may be important targets for screen time interventions in toddlers. Apart from sex, demographic correlates may not be important targets for objectively measured sedentary time and physical activity in toddlers.